Jaw-dropping discovery of earth-like planets revealed to the world. (Research'eu results magazine)
The EU-funded SPECULOOS project has helped to find the most incredible star system to date as seven Earth-sized planets were recently spotted orbiting the nearby star TRAPPIST-1.